How Does Inclusion Impact Employees in Organisations? Literature Review - Alicja Dudek (Acta Universitatis Lodziensis. Folia Oeconomica, 2023)
Purpose: The purpose of this systematic literature review is to review the current state of research on the impact of inclusion in organisations on employees.